Genomic Responses to Climate Change: Making the Most of the Drosophila Model - Rodrigues, Murillo F.; Cogni, Rodrigo (Frontiers in Genetics, 2021)
It is pressing to understand how animal populations evolve in response to climate change. We argue that new sequencing technologies and the use of historical samples are opening unprecedented opportunities to investigate genome-wide responses to changing environments. However, there are important challenges in interpreting the emerging findings. Firstly, it is essential to differentiate genetic adaptation from phenotypic plasticity. Secondly, it is extremely difficult to map genotype, phenotype and fitness. Thirdly, neutral demographic processes and natural selection affect genetic variation in similar ways. We argue that Drosophila melanogaster, a classical model organism with decades of climate adaptation research, is uniquely suited to overcome most of these challenges. In the near future, long term time series genome-wide datasets of D. melanogaster natural populations will provide exciting opportunities to study climate change adaptation over decades and will lay the groundwork for similar approaches in non-model systems.